Statistical Analyses of the Euphrates River Entry and Hydrological Drought Assessment (SDI) - Hussein, Zainab; Khassaf, Saleh I. (Civil Engineering Journal, 2025)
The Euphrates River, a vital water resource in Iraq, has seen a marked decline in flow over the past two decades due to climate change and upstream interventions. The aim of this study is to investigate the impacts of changing rainfall patterns and temperature on the river's water balance, flow regime, and drought index. Results show an annual rainfall decline of 0.15 mm, while maximum and minimum temperatures increased annually by 0.086°C and 0.066°C, respectively, according to the Mann-Kendall trend and Sen’s slope tests. Monthly rainfall generally decreased, except for slight increases in April (0.32 mm) and October (0.018 mm). July 2017 and August 2003 saw peak temperatures of 45.1°C, while January 2008 recorded a minimum of -1.8°C. The box-and-whisker plot revealed high rainfall variability in November and February. River flow dropped by 41%, mainly due to the Turkish GAP project and climate impacts. HEC-DSS software analyzed flow duration over 32 years, and Pearson’s correlation showed low associations between flow rate and temperature (-0.36) and rainfall (0.29). The Drinc program was utilized to calculate the Standardized Drought Index, which identified that the water year 1987–1988 was very wet, while it detected severe droughts in 2014–2015 and 2021–2022. Overall, climate change and upstream dam construction have significantly reduced Euphrates River discharges, intensifying drought conditions in the region. The long-term changes in precipitation and air temperature in the study area support the observed streamflow trends. The findings of this study demonstrate that a cooperative approach to international water management between the riparian states is crucial.